Trace elements and heavy metals in multifloral honeys from Serbia. (September 2019) - Spiric, D; Ciric, J; Teodorovic, V; Nikolic, D; Nikolic, A; Radicevic, T; Jankovic, S
Abstract: This study was to determine the contents and any correlations of As, Cu, Zn, Fe, Cd and Pb in multifloral honeys. Honey, among other bee products, is a good bioindicator since it can reveal the connections between soil, plants and honeybees. Ninety-two samples of multifloral honey were collected from the retail market during the 2018 vegetation season and analyzed to determine mineral content. Analysis of the elements was performed by inductively coupled plasma mass spectrometry (ICP-MS). The most abundant element was Fe, with average concentration of 2.21 ± 1.00 mg/kg, followed by Zn, Cu, Pb, As and Cd. The results obtained show positive correlations: Zn-As, Fe-As, Fe-Cu, Fe-Cd, Cd-Cu and Cd-Pb. Negative correlations are noticeable between Pb and all other minerals except Cd.